Curricular integration of digital technologies in teaching processes - Fernández-Sánchez, María Rosa; Garrido-Arroyo, María del Carmen; Porras-Masero, Isabel (Frontiers in Education, 2022)
The integration of digital technologies in the classroom is a complex and multidimensional process with different dynamics including among others those related to: the digital culture of the centre, competent teachers and students, supportive families and innovative educational programs.This paper presents a Systematic Literature Review (SLR) to analyse how the curricular integration of educational technology in classroom practice has been developed at non-university levels in recent years. The PRISMA 2020 standards have been applied. For the selection of articles, the ERIC database was used, taking as a reference, key concepts from its Thesaurus, related to the objective of the research, performing a temporal search of scientific articles from 2018 to the present. After screening according to the inclusion criteria established by consensus of the researchers, a total of 88 articles were obtained (n=88). The main results point to several variables that should be strengthened to promote the integration of digital technologies in the classroom, among which teacher training stands out as a determining factor, with special emphasis on initial training. This opens a debate about the training that future teachers receive in relation to the integration of digital technologies in the teaching process.